2015
DOI: 10.1016/j.jestch.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimization and modeling of trim cut WEDM operation of commercially pure titanium (CPTi) considering multiple user's preferences

Abstract: a b s t r a c tIn this research work, development of a multi response optimization technique has been undertaken, using traditional utility method in conjunction with the weight assignment concept (for multiple customer's priorities) in trim cut wire electrical discharge machining (WEDM). Pure titanium has been selected as work material for experimentation. The effect of key process parameters such a wire type (zinc coated and uncoated brass wire), pulse on time (T ON ), pulse off time (T OFF ), peak current (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…After completion of MC, TC is performed with low discharge energy along the same path already covered in MC with appropriate wire offset from the surface machined in previous MC. Low discharge energy supplied in TC partially (or even completely) removes various surface irregularities produced in MC [16,17]. Higher wire tension is to be set in TC as compared to MC, because bilateral discharge takes place during MC and the discharge spark imposes symmetrical force on the electrode wire.…”
Section: Introductionmentioning
confidence: 99%
“…After completion of MC, TC is performed with low discharge energy along the same path already covered in MC with appropriate wire offset from the surface machined in previous MC. Low discharge energy supplied in TC partially (or even completely) removes various surface irregularities produced in MC [16,17]. Higher wire tension is to be set in TC as compared to MC, because bilateral discharge takes place during MC and the discharge spark imposes symmetrical force on the electrode wire.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar Jitender and Rupesh [6] (2015) study that multi response optimization technique has been undertaken by using traditional method in finish cut WEDM. In this paper pure titanium used as a work material.…”
Section: Sivanaga Et Al [5] (2014)mentioning
confidence: 99%
“…The detailed functions of each sub-element are available in reference [1,2]. From literature survey, it has been observed that most of the research work carried out on steel and steel alloys, aluminium alloys and titanium alloys [6,9,10]. Less research work has been reported on nickel-base super alloys and therefore it is very much essential to explore WEDM of nickel-base super alloys owing to its industrial importance in gas turbine and aerospace industry.…”
Section: Experimental Setup and Detailsmentioning
confidence: 99%